1994
DOI: 10.1177/00220345940730061501
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thermocycling and Occlusal Force on Adhesive Composite Crowns

Abstract: The aim of this in vitro study was to provide first quantitative data on the marginal adaptation and the required load to fracture of adhesive composite crowns with and without adhesive composite cores. Eighteen caries-free extracted human premolars were restored using fine hybrid composite crowns with margins located entirely in dentin. Six crowns were adhesively luted to dentin stubs, six to endodontically treated teeth with adhesive titanium posts and adhesive composite cores, and six to adhesive composite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 22 publications
2
50
0
6
Order By: Relevance
“…For a fatigue analysis in the FEA study, S - N (stress versus number of cycles to failure) curves of the materials are required. The S - N curve of dentine was referenced from a previous study [27]. Generally, the S - N curves of materials, when no experimental data are available, can be estimated by the following formula (flexural strength ( S f ) versus number of cycles): (0.9 · S f versus 10 3 ), (0.5 · S f versus 10 6 ), and (0.5 · S f versus a number of cycles greater than those tested) [25].…”
Section: Methodsmentioning
confidence: 99%
“…For a fatigue analysis in the FEA study, S - N (stress versus number of cycles to failure) curves of the materials are required. The S - N curve of dentine was referenced from a previous study [27]. Generally, the S - N curves of materials, when no experimental data are available, can be estimated by the following formula (flexural strength ( S f ) versus number of cycles): (0.9 · S f versus 10 3 ), (0.5 · S f versus 10 6 ), and (0.5 · S f versus a number of cycles greater than those tested) [25].…”
Section: Methodsmentioning
confidence: 99%
“…Whereas metal posts may cause non-repairable fracture of the root because of higher stress distribution 8) , fiber posts which have similar elasticity moduli with dentine may overcome this problem 9) . Moreover, several studies in the literature have reported that the application of the posts causes weakening of the roots, in addition to the perforation risk during the preparation of the post space 10,11) . As of yet, there is no established consensus on whether the post length affects the fracture resistance of teeth.…”
Section: Introductionmentioning
confidence: 99%
“…These conditions are believed to simulate, approximately, 5 years of clinical service 35) . This number of cycles have been used in several fatigue studies [12][13][14][15][16]36,37) .…”
Section: Fatigue Model From Previous Feamentioning
confidence: 99%